Impact of perfectionism on the risk of the female athlete triad in collegiate athletes - Brooks, S. G.; Peach, H. D.; Howden, R.; Lowrie, J.; Marino, J. S. (The Journal of Strength and Conditioning Research, 2024)
The female athlete triad is a metabolic syndrome affecting physically active female athletes, especially in high-level athletics. Little is known about the relationship between psychological factors and triad risk. This study aimed to investigate the risk of triad development and the relationship with perfectionistic tendencies in female collegiate athletes. Division I female college athletes (N = 25) (mean age 20.2 ± 1.2) completed the Sport Multidimensional Perfectionism Scale 2, Low Energy Availability in Females Questionnaire, Female Athlete Screening Tool, and medical history surveys. Subjects then received a whole-body dual-energy x-ray absorptiometry scan for body composition and bone density measurements; 60% of subjects were at a moderate risk of developing the triad and 8% were at a high risk. This indicates that there is a high prevalence of triad risk in this population, pointing to the need for better screenings. Subjects with greater perfectionistic tendencies had a greater risk for triad development (r = 0.58), especially when those tendencies manifest in maladaptive dimensions (concerns over mistakes r = 0.75, doubts about actions r = 0.64) (p = 0.05). No significant correlations were established between adaptive dimensions and triad risk, suggesting that athletes with high perfectionistic tendencies that manifest in positive ways may not experience increased risk of the triad or disordered eating. The findings provide a greater understanding of the psychological role perfectionism plays in the development of the triad and help identify behaviors that place athletes at a higher risk.